Ganglion cell complex in early and intermediate age-related macular degeneration: evidence by SD-OCT manual segmentation - Camacho, Pedro (2017)
Purpose: To evaluate ganglion cell layer (GCL) and ganglion cell complex (GCC) thickness manually by spectral-domain optical coherence tomography in subjects with early and intermediate age-related macular degeneration (AMD) in 12 locations on the horizontal meridian. Methods: A total of 450 eyes (specifically, 246 eyes classified as having early/intermediate AMD plus 204 control eyes) were studied. Mann-Whitney U and Kruskal-Wallis tests were used to compare values between the healthy controls and the AMD group and also between the subgroups under study. Diagnostic performance was also compared calculating the areas under the receiver operating characteristic curve. Results: The manual layer segmentation showed clear boundaries between the GCL and the GCC. It was in the temporal GCC that more changes were found. Conclusions: The GCC, especially in the temporal region, allowed the discrimination of differences between various subgroups that have faint variations as well as between early AMD and the first signs of aging.